2014
DOI: 10.1007/s40710-014-0037-3
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological Impacts of Urbanization and Urban Roof Water Harvesting in Water-limited Catchments: A Review

Abstract: Roof water harvesting is a potential source of water for domestic and livelihood uses in water-scarce urban areas of the world such as sub-Saharan Africa (SSA). However, little is known about the hydrological impacts of incorporating roof water harvesting on on-site and downstream hydrology of urbanized catchments. Therefore, the current review investigates the effects of urbanization and urban roof water harvesting on hydrological processes, rainfall-runoff relationships, groundwater recharge and water contam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 65 publications
2
31
0
Order By: Relevance
“…This leads to inefficient rainwater harvesting. In agreement to our finding, a water balance analysis in sub-Saharan Africa (SSA) identified the under-utilization RWH schemes (Gwenzi and Nyamadzawo 2014). This gives rise to a call for water policies in SSA like developed countries, so that people will recognize the role of RWH and use it effectively.…”
Section: Discussionsupporting
confidence: 84%
“…This leads to inefficient rainwater harvesting. In agreement to our finding, a water balance analysis in sub-Saharan Africa (SSA) identified the under-utilization RWH schemes (Gwenzi and Nyamadzawo 2014). This gives rise to a call for water policies in SSA like developed countries, so that people will recognize the role of RWH and use it effectively.…”
Section: Discussionsupporting
confidence: 84%
“…Ishida et al [61] recognized the potential benefit of RWH systems in stormwater management and combined sewer overflow control. Gwenzi et al [83] found that urban RWH systems reduced downstream peak and total discharge, baseflow, and flow velocity. DeBusk et al [84] in a comprehensive review found very little research on the stormwater management benefits of RWH systems.…”
Section: Benefitsmentioning
confidence: 99%
“…Using a RWH system for irrigation also has the potential to improve food security [85][86][87][88], and particularly nutrition among women and children via small-scale domestic gardens [1,83]. Ngigi et al [89] investigated 50m 3 of water storage used in conjunction with drip irrigation kits over 0.2 ha of cropped land, where cash flow was calculated from the improved yield of 4000-5000 kg/ha, showing an increase of 1000 kg/ha.…”
Section: Benefitsmentioning
confidence: 99%
See 1 more Smart Citation
“…An assessment of the impact of land use changes on water resources is one of the recent thrusts in hydrological modelling [1][2][3]. It is expected that approximately 60% of the world's population will be living in urban areas by 2030.…”
Section: Introductionmentioning
confidence: 99%